2021
DOI: 10.1002/mabi.202100043
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Nanoparticle‐Containing Ring‐Implanted Poly(Vinyl Alcohol) Contact Lens for Sustained Release of Hyaluronic Acid

Abstract: Here, a novel ring-implanted poly vinyl alcohol (PVA) contact lens (CL) is fabricated and evaluated as a therapeutic CL with potential of sustained release of hyaluronic acid (HA). HA is loaded on chitosan (CS) nanoparticles (NPs) and then the HA-loaded NPs are dispersed in a ring shape PVA hydrogel which is implanted in the final PVA CL. Results show that HA is successfully loaded on NPs (520 ± 18 nm) with loading efficacy of 87% and loading capacity of 50%. The CL hydrogel has a 275% swelling ratio, no degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…The non-ionic and synthetic biodegradable hydrophilic polymer PVA [53] is approved by the FDA for use in ophthalmic formulations [54]. PVA has been widely used because of its muco-mimetic properties, high water retention capacity, oxygen permeability, and low toxicity [55]. These properties confer to our nanosystems the ability to increase the residence time, and consequently improve the ocular bioavailability, reducing the drainage from lachrymal fluid [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…The non-ionic and synthetic biodegradable hydrophilic polymer PVA [53] is approved by the FDA for use in ophthalmic formulations [54]. PVA has been widely used because of its muco-mimetic properties, high water retention capacity, oxygen permeability, and low toxicity [55]. These properties confer to our nanosystems the ability to increase the residence time, and consequently improve the ocular bioavailability, reducing the drainage from lachrymal fluid [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…[35] Functional nanoparticles with unique properties, such as no/low cytotoxicity, excellent physical/chemical features, and drug-delivery ability, have also been employed to improve/integrate some SCL properties. [51,62,[88][89][90] For example, it has been reported that the nanoparticles were incorporated into CL polymers and gelling systems to enhance mechanical strength and elasticity of CLs. [34] For example, organic dyeencapsulated silica nanoparticles were applied with PHEMA or PDMS to obtain precise biosensing capability, with the detection sensitivity of 0.5-5 mM of blood glucose.…”
Section: Encapsulationmentioning
confidence: 99%
“…[245] The stepwise design for the CL fabrication, from preparing HA-loaded CS NPs to embedding CS NPs into a PVA implant ring to incorporating the ring into the PVA-based hydrogel CLs, has proven effective for controlled HA release for up to 14 days. [245] Regarding the mechanism of DED, it is reported that T cell-mediated inflammation at the ocular surface and periocular tissue could cause this disease. [292] Lifitegrast has shown the ability to lower T-cell activation, reduce cytokine release, and mitigate downstream inflammatory processes.…”
Section: Treatment Of Cataractsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding applications, hydrogels are used mainly in the biomedical field [1]. Thus, they were used as controlled drug release systems [8,9], wound dressing [10], hygiene products [11], contact lenses [12] and tissue engineering [13]. In the latter field, hydrogels can be used as scaffolds, whose functions are to act as extracellular matrix, drug delivery systems and antimicrobial agents during the recovery of the tissue and to support the cells and growth factors that favor the recovery of the tissue [14].…”
Section: Introductionmentioning
confidence: 99%